Pengaruh Kualitas Pelayanan Dan Harga Terhadap Kepuasan Pelanggan di Yanitra Futsal Center, Sidoarjo - Darmawan, Muhammad Agil; Syarif, Muh (Management Department of Economics and Business Of Trunojoyo Madura University, 2023)
Futsal is an indoor football sport with high technical competence, this has an impact on the number of futsal field rental services. Business people must be required to be oriented to consumer satisfaction as the main goal, one of which is the Yanitra Futsal Center. Based on this, an analysis is needed on the effect of service quality and price of Yanitra Futsal Center futsal field rental services themselves on customer satisfaction from users of this service. This study aims to determine the effect of service quality and price on Yanitra Futsal Center customer satisfaction to users of rental services partially or simultaneously. With a Quantitative research method using a questionnaire on Yanitra Futsal Center visitors with independent variables, namely service quality and price, while the dependent variable is Customer Satisfaction. The results of the study are known that visitors to Yanitra Futsal Center there are one hundred people who use Rental Services with an average answer of